Peningkatan Pemahaman Anak Kelompok TK B selama Daring melalui Video Pembelajaran di TK Diponegoro Surabaya - Ida Ayu Puspita Sari; Rofik Jalal Rosyanafi; Fitri Rofiyarti (MOTORIC, 2021)
This study aims to describe the understanding of group B children in Diponegoro Kindergarten Surabaya can be improved through themed learning videos. This research is a type of quantitative descriptive research using classroom action research (CAR). According to Hasnunidah (2017: 68) explains that classroom action research is an action research conducted in the classroom. The population in this study were group B children at Diponegoro Kindergarten Surabaya. By using purposive sampling, the sample is determined intentionally by the researcher based on certain criteria or considerations so that it does not go through the selection process as is done in the random technique (Faisal, 2008:67). The researcher chose 7 children in group B of Diponegoro Kindergarten Surabaya, which consisted of 4 girls and 3 boys. Data collection techniques are an important part of research with the aim of obtaining valid data in a study. In this classroom action research, data collection is done by using observation, interview and documentation techniques. The results of the research described in the previous chapter can be concluded that the provision of learning videos can improve children's understanding of learning in group B Diponegoro Kindergarten, Tambaksari District, Surabaya City. Because it is seen from the results of developmental assessment observations, in the first cycle the success only reached 57.1%. And in the second cycle the average increased to 85.7%.